2006
DOI: 10.1080/08916930600622603
|View full text |Cite
|
Sign up to set email alerts
|

Survival, mortality and causes of death in inflammatory myopathies

Abstract: Although a great improvement has been achieved in the last decades in controlling IM, our study indicates that the mortality rate in this group of patients remains high. Cancer and cardiac involvement are important causes of death, and also prognostic factors for mortality in our group of patients. A careful search for cardiac involvement should be done in every patient with IM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
49
9
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 22 publications
11
49
9
2
Order By: Relevance
“…However, survival time from diagnosis was significantly worse in non-Jo-1 patients compared with Jo-1, SRP and Mi-2 positive patients, making non-Jo-1 a poor prognosis marker. Although the cumulative survival for the entire anti-synAb cohort was similar to previously published reports,14 24 25 the non-Jo-1 patients had lower 5- and 10-year unadjusted cumulative survival rates of 75% and 47%. Non-Jo-1 patients had a significant delay in diagnosis as compared with Jo-1 patients, a key variable negatively impacting their survival.…”
Section: Discussionsupporting
confidence: 86%
“…However, survival time from diagnosis was significantly worse in non-Jo-1 patients compared with Jo-1, SRP and Mi-2 positive patients, making non-Jo-1 a poor prognosis marker. Although the cumulative survival for the entire anti-synAb cohort was similar to previously published reports,14 24 25 the non-Jo-1 patients had lower 5- and 10-year unadjusted cumulative survival rates of 75% and 47%. Non-Jo-1 patients had a significant delay in diagnosis as compared with Jo-1 patients, a key variable negatively impacting their survival.…”
Section: Discussionsupporting
confidence: 86%
“…Of the mortality features from our univariable analyses, those also described in adult IIM studies included older age at illness onset (46, 1013, 29), delay in diagnosis or treatment (4, 5, 10), ILD (6, 12–14), anti-synthetase autoantibodies (8, 9, 30) and dysphagia (6). Our study in JIIM did not identify other important mortality risk factors that have been seen in adult IIM, such as malignancy (4, 5, 1013), cardiac involvement and ischemic cardiovascular disease (6, 8, 11), skin ulcers (10, 13) and male gender (6, 11, 29). The presence of anti-SRP autoantibodies has been found to be a risk factor for death by some investigators (30), but not by others (31); anti-SRP autoantibodies did not appear to increase the risk of death in JIIM in our study.…”
Section: Discussioncontrasting
confidence: 56%
“…Only 3 of these patients had an anti-aminoacyl-tRNA synthetase autoantibody, suggesting that in JIIM there are additional factors contributing to the development of pulmonary disease. In contrast, cardiac disease was a contributing factor to death in only 3 JIIM patients, although it is an important factor in adult studies (6, 11). The cardiac disease in our study is similar to that described in adult myositis studies, which includes rhythm disturbances, conduction abnormalities, pericardial effusion, left ventricular dysfunction, myocarditis, cardiomyopathy and congestive failure (6, 11).…”
Section: Discussionmentioning
confidence: 92%
“…Later work have confirmed this, but shown large variation in mortality rates, probably due to differences in patient selection, classification, loss to follow-up and treatment-related issues [4,5]. Peter and Bohan criteria were applied in eight studies on mortality [3,4,[24][25][26][27][28][29] but only one of them assessed an unselected population-based cohort [3]. This study, which is the largest mortality study to date, identified 248 PM/DM cases diagnosed in Finland from 1969 to 1985 through hospital discharge searches and subsequent case assignment by chart review.…”
Section: Introductionmentioning
confidence: 89%